2014
DOI: 10.1111/cei.12272
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine and chemokine profiles in patients with myasthenia gravis

Abstract: SummaryMyasthenia gravis (MG) is an autoimmune-mediated inflammatory disease of the neuromuscular junction. Previous studies of animal MG models have suggested important roles of cytokines in MG pathogenesis, but adequate studies on cytokines in human MG are lacking. Using a multiplex suspension array system, we measured the serum levels of 27 cytokines/chemokines in 47 anti-acetylcholine receptor antibody-positive patients with MG and 20 normal controls (NC) to investigate the contribution of cytokines/ chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 22 publications
4
49
0
3
Order By: Relevance
“…In this study, patients with MG with thymoma showed higher HMGB1 levels than those without thymoma, which may suggest that HMGB1 is also involved in the pathophysiology of thymus, as reported recently 10. HMGB1 has been shown to stimulate the release of inflammatory cytokines,4 some of which were upregulated in MG 3. Thus, there are potential interactions among these molecules during the inflammatory processes involved in MG pathogenesis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, patients with MG with thymoma showed higher HMGB1 levels than those without thymoma, which may suggest that HMGB1 is also involved in the pathophysiology of thymus, as reported recently 10. HMGB1 has been shown to stimulate the release of inflammatory cytokines,4 some of which were upregulated in MG 3. Thus, there are potential interactions among these molecules during the inflammatory processes involved in MG pathogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, the low-density lipoprotein receptor-related protein 4 (LRP4) antibodies involvement in the pathogenesis of double seronegative MG has been reported 2. T cells, B cells, complement and cytokines play key roles in the pathogenic inflammation in MG 1 3. Inflammation of the neuromuscular junction leads to impaired neuromuscular transmission.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 In this study, no significant difference was observed in the serum levels of IL-17A between pediatric MG patients in the pre-IST period and control subjects, which differed from that in adult MG patients. 31,35 These results suggest an apparent difference in immunological backgrounds between pediatric and adult MG. The absence of coincident increases in serum BAFF and IL-17A levels may be related to negative or low anti-AChR antibody titers in childhood-onset ocular MG.…”
Section: Discussionmentioning
confidence: 83%
“…в нервно-мышечных структурах [101,103,115]. В качестве посредников они принимают участие в дифференцировке иммунокомпетентных и гемо-поэтических клеток, в формировании механизмов межклеточного взаимодействия, лежащих в осно-ве иммунного ответа.…”
Section: роль цитокинов в патогенезе миастении грависunclassified